Black Trumpet, Craterellus cornucopioides (L.) Pers.: Culinary Mushroom with Angiotensin Converting Enzyme Inhibitory and Cytotoxic Activity - Jelena Radović; Aleksandra Leković; Ana Tačić; Margarita Dodevska; Tatjana Stanojković; Tijana Marinković; Čedomir Jelić; Tatjana Kundakovic-Vasović (Polish Journal of Food and Nutrition Sciences)
Nutritional value and chemical composition, including the content of vitamins, fatty acids, 5’-nucleotides and nucleosides and amino acids, as well as biological activities, including antioxidant, angiotensin converting enzyme (ACE) inhibitory and cytotoxic activity of black trumpet ( Craterellus cornucopioides (L.) Pers.) were tested in vitro. C. cornucopioides was low in energy, fat and carbohydrate contents, but rich in dietary fibre, especially β-glucan as well as niacin and α-tocopherol. The content of essential and non-essential free amino acids was 1.49 and 5.48 mg/g dry weight (dw). The nucleosides and 5’-nucleotides were determined at 1.84 and 3.99 mg/g dw, respectively. The share of unsaturated fatty acids (UFAs) was 75.92% with oleic acid as the major UFA. Cyclohexane and dichloromethane extracts expressed significant cytotoxic activity against selected cell lines, human epithelial cervical cancer cells (HeLa), adenocarcinomic human alveolar basal epithelial cells (A549), colorectal cancer cells (LS174) and normal MRC-5 human embryonic lung ﬁbroblast cells (IC50 of 78.3–155.6 μg/mL). ACE inhibitory activity of the aqueous extract was strong with an IC 50 of 0.74 μg/mL. It can be concluded that black trumpet is a good source of nutrients, such as vitamins, dietary fibres, amino acids, nucleotides and fatty acids, which contribute to the overall nutritional value of this fungus with potential for ACE inhibitory activity and use in anti-hypertensive diet.